C-Nail versus plate osteosynthesis in displaced intra-articular calcaneal fractures—a comparative retrospective study - Eva Steinhausen; Wolfgang Martin; Rolf Lefering; Sven Lundin; Martin Glombitza; Bastian Mester; Nikolaus Brinkmann; Marcel Dudda (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Locking plate osteosynthesis via an L-shaped lateral approach is the gold standard in treating displaced intra-articular calcaneal fractures. High complication rates are known for this approach. The most frequent complications are wound edge necrosis and superficial wound infections. To reduce complication rates, a locking intramedullary nail (C-Nail) was developed that can be implanted minimally invasively via a sinus tarsi approach. We compared the postoperative complication rate and the outcome of plate osteosynthesis versus C-Nail in displaced intra-articular calcaneal fractures. Methods All patients with calcaneal fractures who received osteosynthesis with either plate or C-Nail between January 2016 and October 2019 in our institution were retrospectively analyzed. A subgroup analysis was performed with matched pairs (matching Sanders type, age, Böhler’s angle postoperative in normal range, 33 pairs). Endpoints were postoperative complication rate, bone healing, full weight-bearing and functional outcome. Treatment groups were compared using Fisher’s exact test for binary data, and Mann-Whitney U-test for continuous data. A p-value < 0.05 was considered statistically significant. Results One hundred and one calcaneal fractures were included (C-Nail n = 52, plate n = 49). Patients with C-Nail developed significantly less postoperative complications (p = 0.008), especially wound edge necrosis (p < 0.001). Screw malposition was found more often in the C-Nail group. The rates of achieving full weight-bearing as well as bone healing were comparable in both groups, but in each case significant faster in the C-nail subgroup. The results of the matched-pairs analysis were comparable. Conclusions The postoperative complication rate was significantly lower in the C-Nail group. The C-Nail appears to be a successful alternative in the treatment of calcaneal fractures, even in Sanders IV fractures because of the minimal-invasive implantation as well as the high primary stability. Long-term analysis of this new implant including elaboration on functional outcome is planned. Trial registration Deutsches Register Klinischer Studien (DRKS) DRKS00020395 . Date of registration 3 January 2020.